Reinventing Rural Regions - Drabenstott, Mark (Maine Policy Review, 2004)
Rural areas across the United States have been undergoing a fundamental transformation away from their commodity and resource-based economies. This edited keynote speech addresses the question of what’s next for rural areas. Mark Drabenstott, vice president of the Federal Reserve Bank of Kansas City and director of its Center for the Study of Rural America, presents the top 10 ways to reinvent rural regions. He emphasizes competitive niches, cluster development, local amenities, reinventing local governance and, most important, thinking regionally. His remarks were given at a fall 2004 conference sponsored by the University of Maine’s Department of Resource Economics and Policy.